The Anatomy of Teleneurosurgery in China - Xiaohong Gao (International Journal of Telemedicine and Applications)
With its huge population and vast territory, China faces a great challenge in providing modern advanced health care services to all parts of the country. The advances of information communication technologies (ICTs) and the advent of internet have revolutionised the means in the delivery of healthcare via telemedicine to remote and underserved populations, which to a certain extent has been very well exploited in China, especially where 70% peasants residing in the rural areas. This paper reviews the latest development in telemedicine infrastructure in China with the focus on the development of teleneurosurgery, drawing from the results gained from a 3-year networking project between Europe and China on telemedicine (TIME, 2005–2007) funded by European Commission under Asia ICT programme, with an aim to shape up envisages of future medical care in China. Comparison with its counterparts in Europe is also addressed.